Effects of gasoline on haematological parameters of gasoline station workers in Onitsha, Anambra State, Nigeria. - Anyiam, A.F. * , Obi, E. , Ifeanyichukwu, M.O. , Ilo Elochukwu, C. (Sokoto Journal of Medical Laboratory Science)
Gasoline station workers (GSWs) are occupationally exposed to gasoline every day. Our previous study on the toxicological and biochemical profile of GSWs in Onitsha, Anambra state revealed that GSWs are at risk of benzene and lead-mediated toxicity. This was because the GSWs had increased methaemoglobin (used as a biomarker to measure benzene) and blood lead levels. The aim of this paper was to assess the effects of gasoline on the haematological parameters of GSWs in Onitsha, Anambra State, Nigeria. The blood samples of 160 subjects (80 GSWs and 80 controls) were tested for the full blood count (FBC) which includes the total white blood cell count, red blood cell count, mean cell volume, mean cell haemoglobin, mean cell haemoglobin concentration, platelet count, haemoglobin concentration and packed cells volume. Questionnaires were distributed to the GSWs in order to ascertain their duration of exposure to gasoline. The GSWs were divided into three: group A (those exposed for 1 to 6 months) (n=34); group B (those exposed for 6 months to 2 years) (n=22); group C (those exposed for over 2 years) (n=24). Two milliliters of whole blood were collected by venepuncture into EDTA anticoagulated tube and used for the FBC. The FBC was performed within 24 hours of sample collection. Ethical approval was obtained from the ethics committee of the Nnamdi Azikiwe University, Nnewi, Anambra state while the informed consent of the participants was duly sought and obtained. The FBC was analyzed by flow cytometry using the Sysmex Autoanalyzer. The RBC count, MCH, MCHC, PCV and platelet count were significantly reduced in the GSWs when compared with the controls (p<0.05). The RBC count, WBC count, haemoglobin concentration, MCH, MCHC and PCV 7 were highest among group A participants and lowest among group C participants (p<0.05). RBC count, MCH, MCHC, PCV and platelet count were significantly reduced in the test subjects compared to the controls and this could imply ongoing anaemia among the GSWs. The Red Blood Cell and White Blood Cell counts, Haemoglobin, MCH, MCHC and Packed Cells Volume were highest among group A workers and lowest among group C. These findings, just like in the previous one, also suggests that GSWs are highly exposed to toxic gasoline vapor, and reduced haematological parameters among the workers exposed for longer durations suggesting the presence of iron deficiency anaemia and leukocytopenia among these subjects which could consequently affect red blood cell production, functions as well as immunity.